Leksyka związana z mówieniem w listach emigracyjnych Joachima Lelewela pisanych do przyjaciół i znajomych = Lexis connected with speaking in emigration letters written by Joachim Lelewel to his friends and acquaintances - Jaros, Violetta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The object of observation is the lexis referring to the phenomena of speech and speaking, which appears in the correspondence that the scholar-politician conducted in exile in 1831-1860 in France (among others, Paris, La Grange, Tours) and Belgium (Brussels). It constitutes a rich collection of 1496 letters written in Polish (1423), French (65) and German (8), which were collected and published in five volumes by Helena Więckowska.
Keywords: list; Lelewel, Joachim (1786-1861); leksyka związana z mówieniem; 19 w.; letter; lexis related to speaking